Sams Teach Yourself Java 6 in 21 Days - Cadenhead, Rogers; Lemay, Laura (Sams, 2007)
"If you get only one Java book, it should be Sams Teach Yourself Java in 21 Days"--PC Magazine. In just 21 days, you can acquire the knowledge and skills necessary to develop three kinds of programs with Java: applications on your computer, servlets on a web server, and browser-launched Java Web Start applications. No previous programming experience required. By following the 21 carefully organized lessons in this book, anyone can learn the basics of Java programming. Learn at your own pace. You can work through each chapter sequentially to make sure you thoroughly understand all of the concepts and methodologies, or you can focus on specific lessons to learn the techniques that interest you most. Test your knowledge. Each chapter ends with a Workshop section filled with questions, answers, and exercises for further study. There are even certification practice questions. "Sams Teach Yourself Java is one of the best introductions to hands-on Java programming. If you buy one book on Java, this is the one to buy!" - Independent Web Review. Completely revised, updated, and expanded to cover the latest features of Java 6 Learn to develop standalone Java applications, web servlets, JavaServer Pages, and Java Web Start applications Easy-to-understand, practical examples clearly illustrate the fundamentals of Java programming Discover how Swing can help you quickly develop programs with a graphical user interface Find out about JDBC database programming, Internet client/server programming, and XML parsing with the open source XOM class library Covers new features of version 6 such as Java DB, the new relational database that is now a built-in part of Java Rogers Cadenhead is a web application developer who has written 22 books on Internet-related topics, including Sams Teach Yourself Java 2 in 24 Hours. He maintains this book's official website at http://www.java21days.com. Laura Lemay is one of the world's most popular authors on Web development topics. She is the author of the bestselling Sams Teach Yourself Web Publishing with HTML, as well as Sams Teach Yourself Perl in 21 Days. CD-ROM includes: Source code for the examples developed in the book Java SE Development Kit 6 NetBeans IDE 5.5 Bonus materials Category: Java Programming Covers: Java 6 Platform Standard Edition User Level: Beginning - Intermediate.